Limosilactobacillus fermentum KAU0021 Abrogates Mono- and Polymicrobial Biofilms Formed by Candida albicans and Staphylococcus aureus - Irfan A. Rather; Mohmmad Younus Wani; Majid Rasool Kamli; Jamal S. M. Sabir; Khalid Rehman Hakeem; Ahmad Firoz; Yong Ha Park; Yan Yan Hor (MDPI AG, 2023)
Candida albicans and Staphylococcus aureus, representing two different kingdoms, are the most frequently isolated pathogens from invasive infections. Their pathogenic attributes, combined with drug resistance, make them a major threat and a challenge to successful treatments, mainly when involved in polymicrobial biofilm-associated infections. In the present study, we investigated the antimicrobial potential of Lactobacillus metabolite extracts (LMEs) purified from cell-free supernatant of four Lactobacillus strains (KAU007, KAU0010, KAU0021, and Pro-65). Furthermore, LME obtained from the strain KAU0021 (LMEKAU0021), being the most effective, was analyzed for its anti-biofilm property against mono- and polymicrobial biofilms formed by C. albicans and S. aureus. The impact of LMEKAU0021 on membrane integrity in single and mixed culture conditions was also evaluated using propidium iodide. The MIC values recorded for LMEKAU0021 was 406 µg/mL, 203 µg/mL, and 406 µg/mL against planktonic cells of C. albicans SC5314, S. aureus and polymicrobial culture, respectively. The LMEKAU0021 at sub-MIC values potentially abrogates both biofilm formation as well as 24 h mature mono- and polymicrobial biofilms. These results were further validated using different microscopy and viability assays. For insight mechanism, LMEKAU0021 displayed a strong impact on cell membrane integrity of both pathogens in single and mixed conditions. A hemolytic assay using horse blood cells at different concentrations of LMEKAU0021 confirmed the safety of this extract. The results from this study correlate the antimicrobial and anti-biofilm properties of lactobacilli against bacterial and fungal pathogens in different conditions. Further in vitro and in vivo studies determining these effects will support the aim of discovering an alternative strategy for combating serious polymicrobial infections caused by C. albicans and S. aureus.